2023
DOI: 10.1007/s00216-023-04973-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing nanobody and aptamer-based capacitive sensing for detection of interleukin-6 (IL-6) at physiologically relevant levels

Raquel Sánchez-Salcedo,
Rebeca Miranda-Castro,
Noemí de-los-Santos-Álvarez
et al.

Abstract: A major societal challenge is the development of the necessary tools for early diagnosis of diseases such as cancer and sepsis. Consequently, there is a concerted push to develop low-cost and non-invasive methods of analysis with high sensitivity and selectivity. A notable trend is the development of highly sensitive methods that are not only amenable for point-of-care (POC) testing, but also for wearable devices allowing continuous monitoring of biomarkers. In this context, a non-invasive test for the detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…S5 ). However, in our previous work we have demonstrated more extensively the specificity and selectivity of these reagents for their target and their suitability for this type of application 45 , 46 .…”
Section: Resultsmentioning
confidence: 99%
“…S5 ). However, in our previous work we have demonstrated more extensively the specificity and selectivity of these reagents for their target and their suitability for this type of application 45 , 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Nanobodies have unique physicochemical and structural characteristics that make them ideal candidates for the development of diagnostic tests. Sánchez-Salcedo et al [247] presented an electrochemical biosensor for the detection of IL-6 (Figure 23). The authors used a cheap, thin, eight-channel gold sensor array on a flexible substrate as electrodes.…”
Section: Other Types Of Biorecognition Elements Used In Impedimetric ...mentioning
confidence: 99%
“…This electrode reached the high selectivity of TNF-α in the presence of IL-1 and IL-8 interring species and achieved a linear range from 1 to 15 pg mL −1 . Salcedo et al [ 114 ] reported the formation of a mercapto carboxyl self-assembled monolayer on the surface of a gold thin film array, which was used for the immobilization of an IL-6 aptamer capable of IL-6 sensing in the 10–10,000 pg mL −1 range.…”
Section: Electrochemical Detection Of Sepsis Biomarkersmentioning
confidence: 99%